The extent of the school counselor's contribution to enhancing the social communication skill of students with learning difficulties: (Damascus University Journal of arts and humanities sciences, 2024)
The goal of the current research is to identify the role played by the school counselor in schools that include people with special needs (particularly the learning difficulties category), through strategies and activities that contribute to developing and strengthening the social skills that a student with learning disabilities lacks. Accordingly, the current research crystallized by relying on three  Main axes, the first of which is: researching the extent of the school counselor’s familiarity with scientific and medical information related to students with learning difficulties in terms of (the concept, causes, characteristics), the second: the role of the school counselor in enhancing social communication skills, the third: identifying the difficulties that stand in the way of performance.  The school counselor performs his duties within his field of work. Statistical treatments were used commensurate with the research formula, including (one way analysis of variance - ANOVA) test, the reliability of the questionnaire using the Cronbach Alpha equation, and it was applied to the counselors affiliated with the Directorate of Education in the Damascus Countryside, the educational complex in the Qudsaya suburb (those who are in charge of  Their work), which number 132 items. As for the categorical variables on which the research was based (years of experience: less than 5 years, 5-10 years, more than 10 years, scientific and educational qualification (university degree, educational qualification diploma), training courses (did not enroll in a training course, enrolled in a training course). As for the results shown by the study according to the variables that were proposed, they were as follows: There are statistically significant differences regarding the extent to which the school counselor contributes to enhancing the social communication skill of students with learning difficulties according to the academic and educational qualification variable in favor of holders of the educational qualification diploma. - There are statistically significant differences regarding the extent  The contribution of the school counselor in enhancing the social communication skills of students with learning difficulties according to the variable of the training courses for the benefit of the counselors undergoing training courses.
Keywords: School Counselor; Social Communication Skill; Learning Difficulties.